‘Nature Is Something We Can’t Replace’: Mexican Students’ Views of the Landscape They Want to Conserve - Eija Yli-Panula; Eila Jeronen; Gabriela Rodriguez-Aflecht (MDPI, 2022)
The primary aim of this qualitative study was to identify the landscapes that 7−12-year old Mexican students (n = 440) would like to conserve by analysing their drawings. Another aim was to determine the environmental relationship and environmental values of 5th and 6th graders (n = 152) by studying their texts. The data were analysed using mixed methods. In this study, landscape is understood as a visual experience of the environment, comprising the visible features of an area. Based on the results, all of the three main landscapes—nature, social and built—were deemed worth conserving. Beyond students’ immediate environment, the polar regions, North America, Australia and Africa were mentioned; Europe and Asia were not. The landscape drawings were realistic and carefully made, and the descriptions attached to them were clearly written. The environmental approach was mainly humanistic, and aesthetic values were appreciated by both genders. Utilitarian values were mentioned more often by boys than girls. The students’ descriptions reflected their environmental relationship, e.g., concern about nature, showing causal relationships, appreciation and affection. Concern or worry was often accompanied by the mention of human’s responsibility in the students’ texts, but they seldom considered their own activities in relation to the environment. The students depicted threats to nature, but they externalized themselves from the mechanisms threatening nature. In addition, they did not show familiarity with natural processes and scientific terminology. The study reveals that it is not only theoretically important to have distinct values, but these also need to be recognized by individuals. If the humans’ pro-environmental actions are to be promoted through education, it is important to study students’ values, as they may be important barriers to behavioral change. As students showed concern about preserving nature, teachers can discuss environmental values and different ways to take action and make changes with them, in order to avoid anxiety.